Daily Variation in an Intracranial EEG Feature in Humans Detected by a Responsive Neurostimulator System - Duckrow, Robert B.; Tcheng, Thomas K. (Epilepsia (Copenhagen), 2007)
Purpose: Based on the observation that epileptic seizures can occur at specific times of the day, we looked for daily variation in an intracranial electrographic feature used by a responsive neurostimulator system to detect seizures. Methods: A computationally efficient measure of intracranial EEG energy or complexity, the line length baseline, was calculated and reported by an external responsive neurostimulator during a clinical trial of device safety. Data were obtained from 24 consecutive patients with medically intractable epilepsy undergoing intracranial monitoring over 2 to 54 days to localize the seizure onset zone. Measurements from individual subjects made at different times of day over many days were displayed on a single 24‐h cycle and fit with a cosine function to characterize the time of the maximum value. The timing of epileptic seizures was also noted. Results: The time of the maximum line length baseline value had a bimodal distribution with relative peaks at 05:30 and 15:00 hours. The time of the maximum value did not associate with specific brain regions, except that a nocturnal peak was not measured from temporal neocortex. The temporal distribution of maximum values was similar to the timing of epileptic seizures. Conclusion: The line length baseline feature of the intracranial EEG shows daily variation with location specific characteristics within individual subjects.